Uśpiony temat. O (nie)obecności problemu Marca 1968 roku w kinie dokumentalnym okresu PRL - Pietrzak, Maciej (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Pietrzak Maciej, Uśpiony temat. O (nie)obecności problemu Marca 1968 roku w kinie dokumentalnym okresu PRL [Dormant topic. About the absence of the events of March 1968 in Polish documentary films before 1989]. „Images” vol. XXVI, no 35. Poznań 2019. Adam Mickiewicz University Press. Pp. 63–75. ISSN 1731-450X. DOI 10.14746/i.2019.35.03. The vast majority of documentary films relevant to the events of March ‘68 and its consequences were created after 1989, when the abolition of censorship and the opening of previously hidden archives allowed Polish filmmakers to explore previously prohibited topics. The article focuses on the earlier period, and its main objective is to find echos of this political crisis in documentary films created before the collapse of the communist regime in Poland.